2019
DOI: 10.3390/f10080636
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Visitors’ Memorable Tourism Experiences (MTEs) in Forest Recreation Destination: A Case Study in Xitou Nature Education Area

Abstract: Providing memorable tourism experiences (MTEs) plays a crucial role in determining the competitiveness and sustainability of a destination for not only the business sector, but also the environment. Therefore, destination managers face a challenge in identifying, facilitating, and maintaining memorable tourism experiences among visitors. Although MTEs have been increasingly studied, research of the effects of MTEs on word-of-mouth and revisit behavior intentions is still at an early stage of development, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 45 publications
2
66
0
10
Order By: Relevance
“…Participating in tourism activities is one of the ways by which individuals seek meaning about life and experiences that give them a sense of physical, emotional or spiritual fulfilment (Yu et al, 2019). Meaningful experiences are sought by tourists as an inner journey of personal growth and development, self-discovery and inner transformation (Sheldon, 2020).…”
Section: Meaningfulnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Participating in tourism activities is one of the ways by which individuals seek meaning about life and experiences that give them a sense of physical, emotional or spiritual fulfilment (Yu et al, 2019). Meaningful experiences are sought by tourists as an inner journey of personal growth and development, self-discovery and inner transformation (Sheldon, 2020).…”
Section: Meaningfulnessmentioning
confidence: 99%
“…Novelty indicates unique, never-before, once lifetime and new experiences (Kim et al, 2012). Such experiences are remembered and recalled more than ordinary familiar experience (Yu et al, 2019). The opportunity to sample novel foods is a major reason why tourists engage in gastronomy.…”
Section: Noveltymentioning
confidence: 99%
See 1 more Smart Citation
“…Some found that memorable travel experiences play a crucial role in increasing tourist satisfaction and tourist loyalty (Azis, Amin, Chan & Aprilia, 2020). These suggest that the MTE implicitly stems from a satisfying psychological status, and the positively affective nature of such experience has been proved to have impacts on revisiting (Yu, Chang & Ramanpong, 2019). Along with widely reported acceptable reliability and validity of the MTE construct and associated instrument, it had been widely adopted in exploring tourist behavior that is associated with satisfaction and behavioral intentions (Kim & Ritchie, 2014;Chandralal et al, 2015;Zhang, Wu & Buhalis, 2018;Yu et al, 2019).…”
Section: Memorable Tourism Experiencesmentioning
confidence: 99%
“…Trong nghiên cứu này, tác giả kế thừa thang đo trải nghiệm đáng nhớ của Kim et al (2012) bởi 07 thành phần đo lường đã được nhiều nhà nghiên cứu sử dụng ở các bối cảnh khác nhau và đã chứng minh được sự phù hợp của thang đo qua các kết quả nghiên cứu [10]- [15]. Cụ thể các thành phần được hiểu như sau: Sự hưởng thụ là những cảm giác thú vị đem lại sự hứng thú cho du khách; sự mới lạ là cảm giác mới mẻ từ những trải nghiệm mới; văn hóa bản địa là sự tương tác xã hội giữa du khách và người dân địa phương; sự thư giãn là một trạng thái được làm mới, được tiếp thêm sức sống; sự ý nghĩa là cảm giác về vai trò và giá trị; sự tham gia là mức độ tham gia của du khách trong hoạt động du lịch; kiến thức là những thông tin, sự kiện hoặc kinh nghiệm mà du khách nhận được.…”
Section: đặT Vấn đềunclassified